O CENÁRIO EDUCACIONAL NA PRINCESA DA BAIXADA (1920-1960) - Costa, Diulinda Pavão (2012)
Study of the educational institutions, the level of education offered, practices and subjects, which, in diverse time and places have contributed to the process of education in Pinheiro, State of Maranhao, between 1920 and 1960. Is adopted as procedure methodological research literature using a theoretical studies of Dallabrida (2007, 2009), Horta (1994), Souza (1998, 2004, 2008) and others. Os estudos de Martina (1996) and others, who provided subsides to understanding the changes that occur in Catholic Church history and the role played by the Church in education Field. As the of Castro (2007), Coutinho (2005), Fernandes (2003), Motta (2006), Rodrigues (1993) and Saldanha (2008) also contributed to understanding of polical and cultural history of educacional in Maranhão. Was use of the work of Alvim (2006), Gomes (2004), Leite (2000, 2006), Soares (2006) and Viveiros (2007) on the sociopolitical and economical city of Pinheiro. Extensive use is also the document analysis in which the newspaper Cidade de Pinheiro constituted the main document for the organization on the History of Education of the city, along with analysis of the educational legislation, messages, government publications, education regulations. Spear hand to the internal regulations, disciplines schedules, serial ata, employee and students framework, student‟s grade, reports, tumble book and photographs. Use has been made in this walk, Oral History the subjects who experienced the process of schoolling, as students, faculy and staff who, through their memories contributed to the reconstruction of past educational institutions. It appears pinheirense different ways of schooling, being this fact related to the places from which these institutions were organized and the involvement of actors who participated in this process. It is noticed that the school as a producer of its own culture, a historically specific moment, in which subjects have appropriated this cultural environment and reelaboraram in their daily lives, producing social and educational practices in different ways. It is concluded that the current process of schooling in the city went through situations of advances and setbacks, and was contibuted by various social actors who significantly contributed to the formation of youth in the city.